Why CSR communication also has good and negative consequences on a company's social responsibility? - Ismail, Rendi; Karyaningsih; Chin, Jacky; Prabowo, Tyan Ludiana (Jurnal Komunikasi Profesional, 2022)
The disparity between actual CSR initiatives and the extent to which they are conveyed will lead to a negative perception of the company and its operations. A good match between a high level of CSR communication and a high volume of CSR actions, on the other hand, should be helpful. The goal of this research is to determine why CSR communication has both positive and negative effects on corporate social responsibility. In this study, a survey using a quantitative approach was used as the strategy. Individuals exposed to higher levels of communication saw it more strongly (M = 4.01, SD = 0.93) than those exposed to lower levels of communication (M = 2.38, SD = 1.19), according to the results of an independent sample t-test, t (400) = 14.11, p.001. As a result, the deception was effective. In addition, we looked to see if the various experimental groups had differing perspectives on the scope of CSR initiatives. The cross tabulation demonstrated that 84.9 percent of single project participants and 91.0 percent of triple project participants correctly remembered the precise number of CSR activities, 2(1, n = 400) = 102.58, p.001. All CSR communications in this study were provided via screenshots of the company's fictional website, as well as Twitter and Facebook timelines, according to the study's findings. As a result, it's unclear how different modalities of communication affect CSR information processing and result in varied outcomes.